A deep learning radiomics model based on CT images for predicting the biological activity of hepatic cystic echinococcosis - Nijiati, Mayidili; Tuerdi, Mireayi; Damola, Maihemitijiang; Yimit, Yasen; Yang, Jing; Abulaiti, Adilijiang; Mutailifu, Aibibulajiang; Aihait, Diliaremu; Wang, Yunling; Zou, Xiaoguang (Frontiers in Physiology, 2024)
This work aims to explore the potential applications of a deep learning radiomics (DLR) model, based on CT images, in predicting the biological activity grading of hepatic cystic echinococcosis. A retrospective analysis of 160 patients with hepatic echinococcosis was performed (127 and 33 in training and validation sets). Volume of interests (VOIs) were drawn, and radiomics features and deep neural network features were extracted. Feature selection was performed on the training set, and radiomics score (Rad Score) and deep learning score (Deep Score) were calculated. Seven diagnostics models (based on logistic regression algorithm) for the biological activity grading were constructed using the selected radiomics features and two deep model features respectively. All models were evaluated using the receiver operating characteristic curve, and the area under the curve (AUC) was calculated. A nomogram was constructed using the combined model, and its calibration, discriminatory ability, and clinical utility were assessed.12,6 and 10 optimal radiomics features, deep learning features were selected from two deep learning network (DLN) features, respectively. For biological activity grading of hepatic cystic echinococcosis, the combined model demonstrated strong diagnostic performance, with an AUC value of 0.888 (95%CI:0.837-0.936) in the training set and 0.876 (0.761-0.964) in the validation set. The clinical decision analysis curve indicated promising results, while the calibration curve revealed that the nomogram's prediction result was highly compatible with the actual result. The DLR model can be used for predicting the biological activity grading of hepatic echinococcosis.